Money-market segmentation in the euro area: what has changed during the turmoil? - Paolo Zagaglia (Bank of Finland, 2008)
In this paper we study how the pattern of segmentation in the euro area money market has been affected by the recent turmoil in financial markets. We use nonparametric estimates of realized volatility to test for volatility spillovers between rates at different maturities. For the pre-turmoil period, exogeneity tests from VAR models suggest the presence of a transmission channel from longer maturities to the overnight. This disappears in the subsample starting in August 9 2007. The results of the semiparametric tests of Cappiello, Gerard and Manganelli (2005) report evidence of an increase in volatility contagion within the longer end of the money market curve. However this takes place in the lower tail of the empirical distributions.
URN:NBN:fi:bof-20140807477
Keywords: C22; E58; 330; money market; high-frequency data; time-series methods